Sosialisasi Pencegahan Stunting dan Perilaku Hidup Bersih dan Sehat (PHBS) pada Orangtua di Desa Dalangan Kecamatan Tulung Kabupaten Klaten - Amrullah, M. Fikri; Aulia Ramadhani; Suryana Rumpaidus (Jurnal Dharma Indonesia, 2024)
Stunting is a condition of failed growth caused by nutritional deficiencies in children. It is important to understand the contributing factors, such as imbalanced diets and inadequate nutrient intake during the first 1,000 days of life. Clean and healthy lifestyles also play a crucial role in preventing stunting. Practices of hygiene, sanitation, and healthy eating can help optimize children's growth and development. Community education on environmental cleanliness, the importance of clean water, and the role of nutrition in child growth can help reduce the prevalence of stunting. Stunting is one of the major obstacles to child development, and in the Dalangan Village area, Tulung District, Klaten Regency, there are several children affected by stunting, totaling 11 children. Therefore, we, the seventh group of community service students from UNNES, conducted a task assigned to us to create an educational program on stunting and its prevention by distributing the Supplementary Feeding Program (PMT) to these children. Food distribution to the children was carried out on December 17, 2023, in Dalangan Village. The method of implementing this stunting education activity involved delivering materials by students from the Community Service Program at Semarang State University. This activity was well received and positively supported by the Dalangan Village government because it aligns with the village's work program, which aims to raise awareness among the community about the importance of early childhood development and health.